Papel do 18F-FDG PET/CT na avaliação pré-cirúrgica de pacientes com epilepsia refratária do lobo temporal - Manuel Schutze (2013)
Epilepsy is a chronic disease that affects about 50 million people worldwide. Nearly 80% of these people are found in developing regions. The disease is characterized by an increased predisposition to seizures and has a great impact on the lives of patients and their families. Besides the increased mortality, important morbidity and social stigma areassociated with the disease. Pharmacological treatment can control seizures in many cases, but some of the patients continue to present seizures despite use of medication. Between those with temporal lobe epilepsy (TLE), this percentage can be as high as 90%. These patients can benefit substantially from surgical treatment. A few of them, though, do not respond to surgery or show only little improvement. Studies to identify variables (predictive or risk factors) for a good surgical outcome,allow for a more precise surgical indication, in order to obtain the best results for the patient. Modern neuroimaging techniques like positron emission tomography with computed tomography (PET/CT) in conjunction with F-18 fluordeoxyglucose (18F-FDG), make it possible to rapidly and safely evaluate the cerebral metabolism of epilepsy patients.This study aimed to assess the use of automatic 18F-FDG PET image analysis through 3-dimentional stereotactic surface projection (3D-SSP) in the pre-surgical evaluation of patients with refractory epilepsy. A group of 27 patients with refractory LTE and surgical indication and 23 healthy subjects were subjected to a 18F-FDG PET/CT exam, followed bymanual and automatic analysis of the images. The results of the comparison between patients and controls showed significant metabolism differences in the temporal, frontal, occipital and hemisphere mean regions. The asymmetry index for the temporal lobe, which is the difference of metabolism between the left and the right side, showed a sensibility of 53,8% with a specificity of 100% in the identification of patients. The metabolism of the right temporal lobe showed a sensibility of 50% and a specificity of 100% in the identification of the epileptic focus on the right side. These values are bigger than for the manual analysis, which yielded a sensibility of 33,3% and a specificity of 100% for patient identification. The comparison between metabolism values and the clinical variables age of disease onset, disease duration, presence of initial precipitating factors and surgical response did not show any significant relationship. In fact, a large variation of metabolism between patients in the studied regions was observed, which explains the low sensibility of the method in this group. It is likely that differences in metabolism between patients is due to the heterogeneity of their diseases. It is known that TLE is a complex syndrome that can have different causes. Further studies with a larger number of patients are important to reduce the effect of these differences and possibly find relations between metabolism and certain groups of patients.